Gas‐phase fluorination of conjugated microporous polymer microspheres for effective interfacial stabilization in lithium metal anodes - Zihao Li; Lingchen Kong; Cong Peng; Wei Feng (Carbon Energy, 2023)
Abstract Lithium (Li) metal anodes have attracted extensive attention due to their ultrahigh theoretical capacity and low potential. However, the uneven deposition of Li near the unstable electrode/electrolyte interfaces leads to the growth of Li dendrites and the degradation of active electrodes. Herein, we directly fluorinate alkyne‐containing conjugated microporous polymers (ACMPs) microspheres with fluorine gas (F2) to introduce a novel fluorinated interlayer as an interfacial stabilizer in lithium metal batteries. Using density functional theory methods, it is found that as‐prepared fluorinated ACMP (FACMP) has abundant partially ionic C–F bonds. The C–F bonds with electrochemical lability yield remarkable lithiophilicity during cycling. The in situ reactions between the active C–F bonds and Li ions enable transfer of lithium fluoride microcrystals to the solid electrolyte interphase (SEI) layers, guaranteeing effective ionic distribution and smooth Li deposition. Consequently, Li metal electrodes with the fluorinated interlayers demonstrate excellent cycling performances in both half‐batteries and full cells with a lithium bis(trifluoromethanesulfonyl)imide electrolyte as well as a nonfluorinated lithium bis(oxalate)borate electrolyte system. This strategy is highly significant in customizable SEI layers to stabilize electrode interfaces and ensure high utilization of Li metal anodes, especially in a nonfluorinated electrolyte.